Mechanisms of innate immune cells in Metabolic dysfunction-associated steatotic liver disease - Yao, Yao; Wu, Qiong; Fan, Bin; Peng, Xin; Sheng, Mingwei; Wang, Fengmei (Frontiers in Immunology, 2025)
With the continuous increase of the incidence of Metabolic dysfunction-associated steatotic liver disease(MASLD), the proportion of MASLD-driven hepatocellular carcinoma(HCC) is gradually increasing, which will become a heavy burden on global public health. This article summarizes the existing literature and discusses the role of various innate immune cells in the occurrence and development of MASLD, such as cell-cell crosstalk, and uses bibliometric analysis to find current research hotspots and emerging topics, in order to provide valuable reference for scholars studying the direction of MASLD-driven HCC immunity. It also provides a solid foundation for more researchers to join the research direction. And try to inspire researchers in future research to seek breakthroughs in this regard.